Nanofabrication of Ni-incorporated three-dimensional ordered mesoporous carbon for catalytic methane decomposition. Issue 3 (June 2022) - Yang, Xin; Yang, En; Hu, Bo; Yan, Jiahui; Shangguan, Fangna; Hao, Qingqing; Chen, Huiyong; Zhang, Jianbo; Ma, Xiaoxun
Abstract: Incorporation of Ni active species with mesoporous carbon and the resulting composite materials have received much attention due to their nature of flexibility derived from a confluence of metallic and carbonic properties and numerous textural advantages inherited from mesoporous carbon substrates, contributing to their versatility in energy transformation. However, the efficient integration of such composite materials with complementary advantages in properties is still highly desired. Herein, confined growth of Ni(OH)2 nanosheets within three dimensionally ordered mesoporous carbon (3DOMC) by steam-assisted crystallization is propose in this paper. High-crystalline Ni(OH)2 species are found in two forms of confined extra-small nanosheets within the mesopores of 3DOMC and staggered nanosheets over the particles of 3DOMC, which can be reduced to the highly segregative Ni nanoparticles by sufficient reduction. By using as a catalyst for methane decomposition to produce CO x -free hydrogen, Ni/3DOMC contributes a maximum CH4 conversion of 66.5% and H2 output rate of 7.4 mmol. gcat −1 ·min −1 at 850 °C, more superior to the conventional Ni-incorporated active carbon (Ni/AC) catalyst. Moreover, the Ni/3DOMC catalyst also exhibits not only a higher initial reaction rate but also an improved catalytic stability attributed to the abundant homodispersed Ni active species by the highly hybrid structure. It is expected that the flexible component, well-defined structure, and superior CMD performance could promote a great application potential of Ni/3DOMC nanocomposites in catalysis. Graphical Abstract: ga1 Highlights: Efficient loading of Ni(OH)2 nanosheets by using 3DOM carbon as a confined space provider. High-crystalline Ni(OH)2 with dual forms of confined extra-small nanosheets and staggered overgrown nanosheets. Shorter unactivated period but higher initial reaction rate attributed to rapid mass transfer and well-dispersed Ni species. NNi/3DOMC contributes a maximum CH4 conversion of 66.5 % and a maximum H2 output rate of 7.4 mmol.gcat -1 min -1 at 850 °C.